Rejection and Compensation of Periodic Disturbance in Control Systems (The International Journal of Engineering & Information Technology (IJEIT), 2024)
in this paper, a brief introduction to the disturbance rejection methods is given in general and to the periodic disturbance rejection methods in particular. Therefore in the following, methods of using only feedback technique to achieve both set point tracking and periodic disturbance rejection are presented. Also, the interaction problem between the set point design demands and the periodic disturbance rejection is discussed. Then, the interaction is minimized by using a separate feed-forward controller to reject the periodic disturbances as an add-on compensator to the pre-existing set point tracking feedback controller. Furthermore, the idea of the disturbance observer is introduced in general as well as the adaptive periodic disturbance cancelation method.